2013
DOI: 10.1159/000355076
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Problematic Internet Use by the Compulsive Internet Use Scale and the Internet Addiction Test: A Sample of Problematic and Pathological Gamblers

Abstract: This study aims to analyze psychometric properties and validity of the Compulsive Internet Use Scale (CIUS) and the Internet Addiction Test (IAT) and, second, to determine a threshold for the CIUS which matches the IAT cut-off for detecting problematic Internet use. A total of 292 subjects with problematic or pathological gambling (237 men, 55 women) aged 14-63 years and with private Internet use for at least 1 h per working or weekend day were recruited via different recruitment channels. Results include that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 32 publications
3
56
0
2
Order By: Relevance
“…Our results also highlighted that among women (and young adults), time spent online and certain SPIU were better predictors of GPIU, while for men some SPIU would be sufficient, as other authors showed (Durkee et al, 2012;Guertler et al, 2014). This could explain while some authors have suggested that time spent on the Internet was not a good indicator of GPIU (Guertler et al, 2014;Pawlikowski, Nader, et al, 2012).…”
Section: Relationships With Time Spent Onlinesupporting
confidence: 51%
See 3 more Smart Citations
“…Our results also highlighted that among women (and young adults), time spent online and certain SPIU were better predictors of GPIU, while for men some SPIU would be sufficient, as other authors showed (Durkee et al, 2012;Guertler et al, 2014). This could explain while some authors have suggested that time spent on the Internet was not a good indicator of GPIU (Guertler et al, 2014;Pawlikowski, Nader, et al, 2012).…”
Section: Relationships With Time Spent Onlinesupporting
confidence: 51%
“…This could explain while some authors have suggested that time spent on the Internet was not a good indicator of GPIU (Guertler et al, 2014;Pawlikowski, Nader, et al, 2012). This should be further investigated by taking in consideration gender, age and online activities.…”
Section: Relationships With Time Spent Onlinementioning
confidence: 92%
See 2 more Smart Citations
“…Researchers have suggested that identification of the ''problematic Internet user,'' a possible case of IA, is particularly relevant to define target groups for early intervention of IA. 22 DCS model. The Job Content Questionnaire ( JCQ) consists of 22 items for three major scales.…”
Section: Measurementsmentioning
confidence: 99%